2019
DOI: 10.1002/pits.22245
|View full text |Cite
|
Sign up to set email alerts
|

Teacher–student relationships, psychological need satisfaction, and happiness among diverse students

Abstract: Teacher–student relationships have been linked to autonomous motivation and achievement. However, relatively little is known about whether satisfying students’ psychological needs mediates the association between teacher–student relationships and student happiness. Furthermore, this relationship needs to be examined in samples of students from different ethnic and racial backgrounds. In this structural equation modeling study (N = 1,961), we found that teacher–student relationships were positively and moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 63 publications
2
42
0
Order By: Relevance
“…3). Although mean-level differences in need-based experiences exist as a function of demographic differences, the effects of need-based experiences in the prediction of (mal)adjustment are often found to be independent of participants' gender, age (Mackenzie et al 2018), ethnic background (Froiland et al 2019), or socio-economic status (Rodriguez-Meirinhos et al 2019). Similarly, Big Five personality traits (Mabbe et al 2016) and differences in need strength (e.g., Sheldon et al 2001) have not been shown to reliably affect the functional role of need satisfactions on developmental outcomes.…”
Section: Advancementsmentioning
confidence: 99%
“…3). Although mean-level differences in need-based experiences exist as a function of demographic differences, the effects of need-based experiences in the prediction of (mal)adjustment are often found to be independent of participants' gender, age (Mackenzie et al 2018), ethnic background (Froiland et al 2019), or socio-economic status (Rodriguez-Meirinhos et al 2019). Similarly, Big Five personality traits (Mabbe et al 2016) and differences in need strength (e.g., Sheldon et al 2001) have not been shown to reliably affect the functional role of need satisfactions on developmental outcomes.…”
Section: Advancementsmentioning
confidence: 99%
“…For instance, the parent who conveys an expectation that their elementary school child will eventually obtain a doctorate in science also expresses the implicit expectation that they will do well in science classes throughout elementary, secondary, and higher education. Autonomy supportive communication promotes happiness, intrinsic motivation, engagement, creativity, and a variety of other desirable outcomes (Allen et al, 2019;Froiland, 2011a;Froiland et al, 2019). However, parents may need to be prepared for the likelihood that years of autonomy supportive communication will result in a child who thinks for herself and feels comfortable challenging the merit of parents' rules and requests.…”
Section: A New Model For Promoting the Psychological Side Of Parent Imentioning
confidence: 99%
“…Researchers have created several understandings of thriving based on studies with 'WEIRD' populations (Western and/or White, Educated, Industrialized, Rich, and Democratic;Schulz et al 2018), resulting in critiques of their generalizability to other populations (Utseyet al 2008, p. 207). Some of these theories show promise for extending (e.g., Self-Determination Theory and Positive Time Perspective) to multiple ethnicities and socio-economic status levels in the United States (Froiland et al 2019;). However, these models of human thriving from other disciplines, which were not developed specifically for undergraduate engineering students, may not fully apply to this population.…”
Section: Distinct Population: Undergraduate Engineering Studentsmentioning
confidence: 99%